ASSESSMENT OF EFFECTS OF BANDITRY ON MAIZE FARMERS IN LERE LOCAL GOVERNMENT AREA OF KADUNA STATE, NIGERIA - Agyo, Zando B.; Wake, David T. (FUDMA JOURNAL OF SCIENCES, 2025)
This study examined Effects of banditry on maize farmers in Lere Local Government Area of Kaduna State. One of the major threats to the agricultural sector in Nigeria is insecurity from bandits. The sustained terrorist and banditry activities have had negative impacts on agricultural activities and farming system which led to loss of lives and economic losses. Descriptive survey design was used to collect and analyzed data which consists maize farmers in Lere Local Government Area, questionnaire was used to collect information from the respondents. Based on the result, most of the respondents are male. Most of the respondent (60 %) strongly agreed that bandits often target farms to steal valuable crops leading to significant financial losses which is positive. 51 % respondents strongly agreed that bandit attacks often result in the destruction of farm infrastructure, including barns, storage facilities, and equipment. Majority (65 %) of the respondents strongly agreed that presence of banditry forces farmers to invest in security measures such as hiring guards, installing fencing, and using surveillance equipment. 74 % of the respondents strongly agreed that frequent bandit attacks disrupt the supply chain, making it difficult for farmers to transport their goods to market. 48 respondents representing 48 % strongly agreed that banditry fosters an atmosphere of fear and mistrust within rural communities. Bases on the study it was recommended that community or people of the area should try as much as possible to assist in strengthen the security system in the area, the community leader should...
Keywords: Effects; Banditry; Maize farmers; Surveillance equipment